The intriguing role of Rifaximin in gut barrier chronic inflammation and in the treatment of Crohn's disease. (3rd June 2018) - Lopetuso, Loris R.; Napoli, Marco; Rizzatti, Gianenrico; Gasbarrini, Antonio
ABSTRACT: Introduction : The gastrointestinal tract acts as a functional unit organized as a semipermeable multilayer system, in which commensal gut microbiota represents the anatomical barrier. Recently, several studies have highlighted the involvement of gut microbiota in inflammatory bowel diseases (IBD) pathogenesis, in sustaining gut barrier chronic inflammation, and in conditioning disease course and therapeutical response. This evidence provides a rationale for treating patients with gut microbiota modifiers. Among these, Rifaximin represents a non-traditional antibiotic able to act as a 'eubiotic' on intestinal barrier. Area covered : The purpose of this narrative review is to explore the impact of Rifaximin on gut barrier and gut microbiota in IBD, in particular in Crohn's disease (CD), and to analyze its potential therapeutic applications. Expert opinion : The possibility of a beneficial activity of Rifaximin in chronic intestinal inflammation and CD has been debated and evaluated with different studies having obtained promising but still preliminary data. Larger trials are therefore needed. This gut-specific antibiotic could represent an alternative to systemic antibiotics thanks to its favorable safety profile and promising efficacy data. Rifaximin could exert, when appropriate, a synergic effect with immunomodulators in IBD, acting on both the microbial and the immunological sides of gut barrier impairment.